2005
DOI: 10.1074/jbc.m501650200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-independent Regulation of Metabotropic Glutamate Receptor 1 Signaling Requires G Protein-coupled Receptor Kinase 2 Binding to the Second Intracellular Loop

Abstract: Metabotropic glutamate receptors (mGluRs) are members of a unique class of G protein-coupled receptors (class III) that include the calcium-sensing and ␥-aminobutyric acid type B receptors. The activity of mGluRs is regulated by second messenger-dependent protein kinases and G protein-coupled receptor kinases (GRKs). The attenuation of both mGluR1a and mGluR1b signaling by GRK2 is phosphorylation-and ␤-arrestin-independent and requires the concomitant association of GRK2 with both the receptor and G␣ q/11 . G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
1
42
1
Order By: Relevance
“…The crystal structure of GRK2 (Tesmer et al, 2005) suggests that it may simultaneously sequester both active G␣ q and free G␤␥, which, in addition to receptor phosphorylation, may increase the strength and effectiveness of GRK2-mediated receptor regulation. We and others have demonstrated that GRK2-regulated GPCRs, such as the H1 histamine (Iwata et al, 2005), M 1 mAChR (Willets et al, 2005), metabotropic glutamate (Dhami et al, 2005), and A, cells were transfected with SMARTpool siRNA and harvested 72 h later. Blots were incubated with a monoclonal antibody for arrestin-2 that cross-reacts with arrestin-3.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of GRK2 (Tesmer et al, 2005) suggests that it may simultaneously sequester both active G␣ q and free G␤␥, which, in addition to receptor phosphorylation, may increase the strength and effectiveness of GRK2-mediated receptor regulation. We and others have demonstrated that GRK2-regulated GPCRs, such as the H1 histamine (Iwata et al, 2005), M 1 mAChR (Willets et al, 2005), metabotropic glutamate (Dhami et al, 2005), and A, cells were transfected with SMARTpool siRNA and harvested 72 h later. Blots were incubated with a monoclonal antibody for arrestin-2 that cross-reacts with arrestin-3.…”
Section: Discussionmentioning
confidence: 99%
“…GRK2-mediated attenuation of mGluR1a signaling occurs as the consequence of the concomitant association of the kinase with the second intracellular loop domain of the receptor and Gaq (Dhami et al, 2004(Dhami et al, , 2005Dhami and Ferguson, 2006;Ferguson, 2007). We investigated the effect of three intracellular loop 2 SNVs on the association of GRK2 with mGluR1a.…”
Section: Discussionmentioning
confidence: 99%
“…Desensitization of mGluRs is complex as mGluR1a desensitization includes phosphorylationdependent and -independent mechanisms (Dhami et al, 2004(Dhami et al, , 2005Dhami and Ferguson, 2006;Ferguson, 2007;Ribeiro et al, 2009). G protein-coupled receptor kinase 2 (GRK2)-mediated mGluR1/5 desensitization is phosphorylation independent, whereas second-messenger-dependent kinases phosphorylate the second intracellular loop and carboxyl-terminal tail domains of mGluR1a to mediate phosphorylation-dependent mGluR desensitization (Francesconi and Duvoisin, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of GRK2 to G␣q/11 effectively terminates transduction of the G␣ signal (3, 5-7). This phosphorylation-independent mechanism has now been implicated in the regulation of several Gq/11-coupled receptor signaling events (2,8,9).…”
mentioning
confidence: 99%
“…Binding of GRK2 to G␣q/11 effectively terminates transduction of the G␣ signal (3, 5-7). This phosphorylation-independent mechanism has now been implicated in the regulation of several Gq/11-coupled receptor signaling events (2,8,9).Amiloride-sensitive epithelial Na ϩ channels (ENaC) play an important role in regulating Na ϩ and fluid homeostasis, maintaining blood pressure (10) and regulating volume of the alveolar fluid (11). ENaC is expressed in a variety of tissues including the renal collecting duct, the distal colon, the lungs and the ducts of exocrine glands.…”
mentioning
confidence: 99%